Structural and improved dielectric properties of Bismuth pyrochlores containing interchangeable Ta5+ and Nb5+ cations - Khaw, C.C.; Tan, P.Y.; Tan, K.B.; Ananda Murthy, H.C. (Malaysian Institute of Chemistry, 2024)
The pyrochlore structure demonstrates great structural flexibilities, compositional variables, and diverse electrical properties suitable for various electrical applications. This study aimed to synthesise novel pyrochlore phases with improved dielectric performance in the Nb-doped bismuth magnesium tantalate (BMT) system. A complete subsolidus solution was successfully prepared by solid-state reaction through a one-to-one replacement of Ta5+ by Nb5+ with the proposed chemical formula of (Bi3.50Mg0.50)(Mg1.30NbxTa2.70-x)O13.80 (0.00 ≤ x ≤ 2.70). Such doping mechanism implies that both isomorphous Nb5+ and Ta5+ are highly interchangeable due to their similar crystallo-chemical structures and ionic radii. The incorporation of Nb5+ into the BMT host structure resulted in the gradual increase of lattice parameters from 10.5610 (9) to 10.5809 (10) Å. The well-connected polyhedral grains in the range of 2.25–20.00 μm supported their average relative densities of above 80%. The Nb dopant was concluded to significantly enhance the dielectric performance of BMT pyrochlores, i.e., more than two-fold increase of dielectric constant, ε' from 81 to 195, while dielectric loss, tan δ is retained low in the order of 10-3 © 2024 Malaysian Institute of Chemistry. All rights reserved.